Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve for [tex]\( p \)[/tex] and [tex]\( q \)[/tex] in the given equation [tex]\( x^2 + 8x + 10 = (x + p)^2 + q \)[/tex], we will proceed step by step.
1. Step 1: Expand [tex]\( (x + p)^2 \)[/tex]
Start by expanding the expression on the right-hand side of the equation:
[tex]\[ (x + p)^2 = x^2 + 2px + p^2 \][/tex]
Therefore, we can rewrite the right-hand side of the equation as:
[tex]\[ (x + p)^2 + q = x^2 + 2px + p^2 + q \][/tex]
2. Step 2: Set the expanded form equal to the original equation
Now, we equate the left-hand side [tex]\( x^2 + 8x + 10 \)[/tex] with the expanded form [tex]\( x^2 + 2px + p^2 + q \)[/tex]:
[tex]\[ x^2 + 8x + 10 = x^2 + 2px + p^2 + q \][/tex]
3. Step 3: Compare coefficients
To solve for [tex]\( p \)[/tex] and [tex]\( q \)[/tex], compare the coefficients of [tex]\( x \)[/tex] and the constant terms on both sides.
- Coefficient of [tex]\( x^2 \)[/tex]:
On both sides, the coefficient is 1, so this term cancels out.
- Coefficient of [tex]\( x \)[/tex]:
[tex]\[ 8 = 2p \][/tex]
Solve for [tex]\( p \)[/tex]:
[tex]\[ p = \frac{8}{2} = 4 \][/tex]
- Constant terms:
[tex]\[ 10 = p^2 + q \][/tex]
Substitute [tex]\( p = 4 \)[/tex] into this equation:
[tex]\[ 10 = 4^2 + q \][/tex]
Which simplifies to:
[tex]\[ 10 = 16 + q \][/tex]
Solving for [tex]\( q \)[/tex]:
[tex]\[ q = 10 - 16 \][/tex]
Therefore:
[tex]\[ q = -6 \][/tex]
4. Step 4: Conclusion
We have found the values of [tex]\( p \)[/tex] and [tex]\( q \)[/tex]:
[tex]\[ p = 4 \][/tex]
[tex]\[ q = -6 \][/tex]
Thus, the solution is:
[tex]\( p = 4 \)[/tex] and [tex]\( q = -6 \)[/tex].
1. Step 1: Expand [tex]\( (x + p)^2 \)[/tex]
Start by expanding the expression on the right-hand side of the equation:
[tex]\[ (x + p)^2 = x^2 + 2px + p^2 \][/tex]
Therefore, we can rewrite the right-hand side of the equation as:
[tex]\[ (x + p)^2 + q = x^2 + 2px + p^2 + q \][/tex]
2. Step 2: Set the expanded form equal to the original equation
Now, we equate the left-hand side [tex]\( x^2 + 8x + 10 \)[/tex] with the expanded form [tex]\( x^2 + 2px + p^2 + q \)[/tex]:
[tex]\[ x^2 + 8x + 10 = x^2 + 2px + p^2 + q \][/tex]
3. Step 3: Compare coefficients
To solve for [tex]\( p \)[/tex] and [tex]\( q \)[/tex], compare the coefficients of [tex]\( x \)[/tex] and the constant terms on both sides.
- Coefficient of [tex]\( x^2 \)[/tex]:
On both sides, the coefficient is 1, so this term cancels out.
- Coefficient of [tex]\( x \)[/tex]:
[tex]\[ 8 = 2p \][/tex]
Solve for [tex]\( p \)[/tex]:
[tex]\[ p = \frac{8}{2} = 4 \][/tex]
- Constant terms:
[tex]\[ 10 = p^2 + q \][/tex]
Substitute [tex]\( p = 4 \)[/tex] into this equation:
[tex]\[ 10 = 4^2 + q \][/tex]
Which simplifies to:
[tex]\[ 10 = 16 + q \][/tex]
Solving for [tex]\( q \)[/tex]:
[tex]\[ q = 10 - 16 \][/tex]
Therefore:
[tex]\[ q = -6 \][/tex]
4. Step 4: Conclusion
We have found the values of [tex]\( p \)[/tex] and [tex]\( q \)[/tex]:
[tex]\[ p = 4 \][/tex]
[tex]\[ q = -6 \][/tex]
Thus, the solution is:
[tex]\( p = 4 \)[/tex] and [tex]\( q = -6 \)[/tex].
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.